Police and Thieves, Gunmen and Drunks: Problems with Men and Problems with Society in Papua New Guinea - Macintyre, Martha (The Australian journal of anthropology, 2008)
The image of the ‘man with a gun’ is pervasive in Papua New Guinea and connotes not only the state's capacity to use force, but that of men to resist and subvert state control. At the same time, the association of beer and marijuana with both modernity and violent masculine behaviours provides the context, the justification and the forms of homosocial activities involving violence. In this paper, I explore the ambiguities surrounding guns as instruments of state force and as symbols of masculine autonomy in so-called ‘weak states’ by examining some stories about the ways that guns are acquired for illegal activities. In particular, I shall discuss the ways that guns and beer are instruments of violence and potency for police, tribal warriors and criminals as well as some of the means whereby men gain access to new forms of power. Drawing on ethnographic research with young men in New Ireland Province, the paper will deal specifically with the ways that adolescent boys construe ‘modern masculinity’.